Cruzando fronteiras e negociando lealdades: índios missioneiros entre os domínios ibéricos de Mojos, Chiquitos e Mato Grosso (c. 1767-1800) - Francismar Alex Lopes de Carvalho (Centre de Recherches sur les Mondes Américains, 2012)
This article examines some impacts of Iberian reformist policies on frontier peoples of South American central plains. It focuses on circumstances that propitiated that Indians from the Spanish missions of Mojos and Chiquitos crossed borders between two empires. After the expulsion of the Jesuits from Spanish America in 1767, the reformism in those missions intensified the labor system and removed benefits and privileges. The cabildos indigenas sent petitions to the governors and, when no assisted, they promoted desertions to the Portuguese capitania of Mato Grosso. Indeed, these frontiers may have been more porous and permeable than was supposed, as well as the monarchic loyalties, it seems, was more negotiable and manipulable.